Alarmingly high prevalence of addictive screen use behaviour among under thirteen children: a cross sectional study in Mumbai - Paranjape, Raghav M.; Raul, Shreeya K.; Rao, Shirish R.; Mhatre, Pauras P.; Adarkar, Shilpa A. (International Journal of Contemporary Pediatrics, 2022)
Increasing amount of discretionary (non-homework) screen time (DST) has raised significant concerns over the addictive potential of screen-based media and psychiatric dimension children’s health. This study was undertaken to find the prevalence of addictive screen use behaviour in children under the age of 13 years, and its association with the type of content consumed. A cross-sectional study was conducted in Mumbai metropolitan region (MMR) in which 154 parents from 4 schools were interviewed using a pre-validated questionnaire. Data was analyzed using SPSS v26.0, chi-square test and unpaired t test were used at significance level of p<0.05. 18% of the children were found of have addictive screen use behaviour and it was found to be significantly associated with playing shooting and fighting games (p<0.05). Prevalence of addictive screen use behaviour is alarming among under 13 children. Interventions to tackle this concern must be urgently undertaken.